COMMUNITY PARTICIPATION IN COMMUNITY DIVERSION PROGRAM - Paramta Ayuningtyas (Universitas Negeri Semarang, 2018)
Community Members had been participated in CDP as participant of fammily group discussion, guidance, supervision and empowerment of offender fammily. This research had purposes to know how important Community Members (Community Leaders, Religious Leaders, and Teacher) had been participated in Community Diversion Program (CDP) as effective solution to solve Juvenille Delinquency and how its community participation model on running CDP. The method used in this research is qualitative method and socio legal approach. In this research can be concluded that Community Members had important roles in CDP as partner of Parole Officer and other Law Enforcement Apparatus to held Community Based Corrections (CBC), is all about activities which refered to therapy program, supports, and supervision for offender. Partnership Model is community participation model which took high level of community participation in development program, such as CDP. So Community Diversion Program could be alternative solution to increase effectiveness of law enforcement in Juvenile Justice System in Indonesia, those effectiveness are decreasing number of recidivism and law enforcement resulted justice, utility and certainty.